OPTIMASI DESAIN ISOLASI RUANG PALKA IKAN KM. BERKAH 9 GT UNTUK MENGURANGI LAJU PERPINDAHAN PANAS - Budiarto, Untung; kiryanto, Kiryanto (Department of Naval Architecture - Diponegoro University, 2010)
Fishing vessel Cantrang 9 GT Type belong toÂ Mr.H.Jupri, a fishing vessel ownership at Wedung Demak, still use block ice for cargo hold in which each its wall insulation on Sterofoam. This insulation to be used because is cheapest although it investigated to overall of total cost is rated still not optimal enough. In this final project optimizes original design of cargo hold to replaced by new design alternative in its insulation part with using insulation subtance Polyurethane. Chosen 3 thickness variation of insulations, they are 5 cm (called; Design A), 10 cm (Design B) and 15 cm (Design C). The variation used as principal data to calculate the cooling load, afterward theÂ calculation of block ice needed which to be used for ship operational. Based on insulation and equipment of refrigeration system data, will be calculated economically that is included investation Cost and Operational Cost. The result of calculation of each alternative design that based on economically calculated Method. design C have most advantages economically than others about 36,95 % to original design.Â